Bilateral Carotid Body Tumors - Shrestha, U.K.; Shrestha, B.M.S.; Ghimire, R.K.; Joshi, P.R.; Amatya, S.L. (Journal of Institute of Medicine Nepal, 2007)
Introduction: Carotid body tumor is a rare neoplasm of the carotid body. Surgical excision of carotid body tumor is a challenge to the surgeon. Case report: A 23-years-old patient was diagnosed as having bilateral carotid body tumors at the bifurcation of the common carotid arteries. Resections were done at 6 weeks interval with minimal morbidity in first excision and no morbidity in second operation. Conclusion: Color Doppler study and computerized tomography are very good non-invasive tools for the diagnosis. Journal of Institute of Medicine Vol.28(1) 2006